The Effect of Inhalation Smoking by Narghile on Some Parameters Biochemistry - Noor Essam Abdul Rezaq (Journal of Global Pharma Technology, 2018)
The present study included 50 sample collected  different of Iraq.25 sample narghile smoker men group  and 25 control men  group show the results increase significant in MDA, ALT, AST and LDH in narghile smoker men group  when compared with control men  group , while decrease significant in C.K and ACHE in narghile smoker men group  when compared with control men  group   Keywords: Nargile, Oxidative stress, MDA, LDH , CK , ACHE , ALP , ALT and AST.